Game-assisted learning for children with Autism Spectrum Disorder - Siti Faatihah Mohd Taib (2017)
This report discusses about game-assisted learning for children with Autism Spectrum Disorder (ASD) and the project undertaken to design a game to cater to the development of the planning executive function of the ASD children. A brief introduction on Autism Spectrum Disorder has highlighted the use of computer-aided technology in the learning and development of children with ASD. This paper discusses the methodology implemented in the game design and creation of the supermarket route-planning game which aims at training and keeping track of the progress of the ASD child’s planning executive function. The analysis and review of the methodology has also been deliberated together with the challenges faced by the author. Concluding this report is the future works and recommendations to further improve this project’s game design and implementation.